2021
DOI: 10.1038/s41372-021-01232-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of venous thromboembolism among infants in children’s hospitals in the United States: a retrospective Pediatric Health Information Study

Abstract: Objectives Examine: (1) Prevalence of diagnosed venous thromboembolism (VTE) in infants <6 months discharged from U.S. NICUs; (2) Associations between sociodemographic and clinical factors and VTE; (3) Secondary outcomes related to VTE. Study design Multivariable logistic regressions examined associations between VTE and sociodemographic and clinical factors among infants <6 months discharged from Pediatric Health Information System (PHIS) NICUs between 2016 and 2019. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In adolescents, the incidence equals that of young adults, probably due to hormonal status, the use of contraceptives, pregnancy in young women, obesity, and smoking [ 10 , 11 ]. A recent prospective study demonstrated a prevalence of 1.35% of venous TEs in infants aged < 6 months discharged from Neonatal Intensive Care Units in the United States, with the main clinical risk factors being CVL, total parenteral nutrition, mechanical ventilation, infection, surgery, and extra-corporeal membrane oxygenation [ 12 ]. Given the increased incidence and the consequences on morbidity and mortality of TEs in children, applying age-specific models for risk stratification can be crucial to finding patients at a higher risk for TEs, who can benefit from anti-coagulation prophylactic regimens.…”
Section: Discussionmentioning
confidence: 99%
“…In adolescents, the incidence equals that of young adults, probably due to hormonal status, the use of contraceptives, pregnancy in young women, obesity, and smoking [ 10 , 11 ]. A recent prospective study demonstrated a prevalence of 1.35% of venous TEs in infants aged < 6 months discharged from Neonatal Intensive Care Units in the United States, with the main clinical risk factors being CVL, total parenteral nutrition, mechanical ventilation, infection, surgery, and extra-corporeal membrane oxygenation [ 12 ]. Given the increased incidence and the consequences on morbidity and mortality of TEs in children, applying age-specific models for risk stratification can be crucial to finding patients at a higher risk for TEs, who can benefit from anti-coagulation prophylactic regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Estimated rates of venous thromboembolism in infants who are admitted to the neonatal intensive care unit (NICU) range from 0.1 to 5.9%. The most common locations for venous thromboembolism to occur in infants include the lower extremities and the vena cava or other thoracic veins [1]. Critically ill infants are at a higher risk than the general pediatric population for thrombotic complications, and multiple factors including central lines, congenital heart disease, disseminated intravascular coagulation, sepsis, prolonged hospitalization, and liver dysfunction exacerbate that risk [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal venous thrombosis is a rare condition that occurs most often in infants born between the 22nd and 27th week of pregnancy [1]. Up to 90% of venous thromboembolisms are iatrogenic and are associated with central venous catheters [2,3]. Other predisposing factors are mechanical ventilation, infections with cardiotropic viruses (e.g., parvovirus B19, influenza virus, human immunodeficiency virus, cytomegalovirus, herpes simplex virus) [4], hospital stays equal or longer than five days [5], and genetic mutations (e.g., Factor V, Factor II, methylenetetrahydrofolate reductase (MTHFR) genes, protein S or C deficiencies) [6].…”
Section: Introductionmentioning
confidence: 99%